PERAN CLOSED CIRCUIT TELEVISION (CCTV) DALAM MENINGKATKAN KEAMANAN DI KAMPUS STIE GANESHA - Astanto, Tri; Saefullah, Aep; Ardianto, Marsidi; Pambudi, Ryan; Sarkum, Sarkum; Ahhari, Ayu; Saputri, Haria (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
Closed Circuit Television (CCTV) is an essential tool for guarding and monitoring locations. CCTV is an additional tool for security, and is widely used in shops, offices, and even housing. CCTV on campus is also used to prevent, monitor, and improve the performance of lecturers, students and employees. This research aims to explore and reveal the utilization of this media in depth. The research was conducted for 2 months from June to July 2023. This research methodology adopts a qualitative descriptive approach. Data were obtained through interviews, observations, and literature studies. The findings of this study indicate that the installation of CCTV cameras on the STIE Ganesha campus is effective in carrying out three main functions: preventing, monitoring, and improving the performance of lecturers and students. The installation of CCTV plays a role in supporting lecturers in improving the quality of teaching. The implications of this research provide encouragement to continue exploring innovative ways of utilizing technology to support and enrich the educational experience on campus.